PENGARUH EKSTRAK KULIT BAWANG MERAH DALAM MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera litura F.) SECARA IN VITRO - Yunda Gusriani; BENAULI, ARKHIADI; SULASTRI, YUSTINA SRI (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2023)
This research was conducted to determine the dose of shallot skin extract that is effective for controlling Spodoptera litura F. This research was carried out for 2 months at the Biology Laboratory, Faculty of Agriculture, Santo Thomas Catholic University, Medan. The research design used was a Non-Factoral Completely Randomized Design (CRD) consisting of five treatments and each treatment was repeated four times to form 20 experimental units of Red Onion Skin Soaking (K), namely: K0 = 0% (Control), K1 = 20 gr/liter of water, K2 = 40 gr/liter of water, K3 = 60 gr/liter of water, and K4 = 80 gr/liter of water. The parameters observed were pest mortality, 50% death time and larval behavior after application. From the research results, it can be seen that administering shallot skin extract at the highest dose, namely 80 g/L, can be quadratically used as a botanical insecticide to control S. litura pests with a death time of 27 hours